Answer:
Hence, the
and approximately value of
is
.
Given :
![my''+cy'+ky=F(t), y(0)=0, y'(0)=0,](https://img.qammunity.org/2022/formulas/mathematics/college/otopqcc1lgtn6tyvpcjddx9qmg2py9rcw9.png)
Where
kilograms
kilograms per second
Newtons per meter
Newtons
Explanation :
(1)
Solve the initial value problem.
![y(t)](https://img.qammunity.org/2022/formulas/mathematics/college/2eot510f1tetv027mkrnbydjzeivsbqmfp.png)
![my''+cy'+ky=F(t), y(0)=0, y'(0)=0,](https://img.qammunity.org/2022/formulas/mathematics/college/otopqcc1lgtn6tyvpcjddx9qmg2py9rcw9.png)
![\Rightarrow 2y''+8y'+80y=20\sin (6t)](https://img.qammunity.org/2022/formulas/mathematics/college/tnt17o1a9kxhadncivra7dlrp1424x67hu.png)
![\Rightarrow y''+4y'+40y=10\sin (6t)](https://img.qammunity.org/2022/formulas/mathematics/college/jop4v1eelbiicxuli5q03tmgeowd5zshdj.png)
Auxilary equations :
![F(t)=0](https://img.qammunity.org/2022/formulas/mathematics/college/w98pgoq9nrjywb8g7gyo8p9nk6x6rjcs5q.png)
![\Rightarrow r^2+4r+40=0](https://img.qammunity.org/2022/formulas/mathematics/college/ptudopdhmcbhbfgea2ey23501jbetydh5s.png)
![\Rightarrow r=(-4\pm√(4^2-4* 1* 40))/(2* 1)](https://img.qammunity.org/2022/formulas/mathematics/college/eehzkthiqwkf5v2oee3xqfbn9wcwak89ap.png)
![\Rightarrow r=(-4\pm√(16-160))/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/z98klhmyw0ds6hv7azo39j9cus59or64ve.png)
![\Rightarrow r=(-4\pm√(-144))/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/d0uvedl139ocvbgug0qvuhe6uzb4xdg0e4.png)
![\Rightarrow r=(-4\pm12i)/(2)](https://img.qammunity.org/2022/formulas/mathematics/college/qu0f64plnasu2zmvatkiftzhw31cxeoz96.png)
![\Rightarrow r=-2\pm6i](https://img.qammunity.org/2022/formulas/mathematics/college/grc0fd4eisdnwdv9r3kxqm9j6n7aqlu6yi.png)
The complementary solution is
![y_c=e^(-2t)\left(c_1\cos 6t+c_2\sin 6t\right)](https://img.qammunity.org/2022/formulas/mathematics/college/7mzb4u72hy821gmbr1yi6fjzv6a8jqr02j.png)
The particular Integral,
![y_p=(1)/(f(D))F(t)](https://img.qammunity.org/2022/formulas/mathematics/college/rdovgi7thrpfcr7v6ehupyh46vvfo3grwn.png)
![y_(y) &=(1)/(D^(2)+4 D+40) 25 \sin (6 t) \\\\ y_(y) &=(25)/(-6^(2)+4 D+40) \sin (6 t) \quad\left(D^(2) \text { is replaced with }-6^(2)=-36\right) \\\\y_(y) &=(25)/(4 D+4) \sin (6 t) \\\\y_(y) &=(25)/(4(D+1)) \sin (6 t) \\\\y_(y) &=(25(D-1))/(4(D+1)(D-1)) \sin (6 t) \\\\y_(y) &=(25(D-1))/(4\left(D^(2)-1\right)) \sin (6 t) \\\\y_(y) &=(25(D-1))/(4(-36-1)) \sin (6 t) \\\\y_(y) &=-(25)/(148)(D-1) \sin (6 t) \\y_(y) &=-(25)/(148)\left((d)/(d t) \sin (6 t)-\sin (6](https://img.qammunity.org/2022/formulas/mathematics/college/yta21zx8hqxgaoet3ul572abv9gf9e2j33.png)
Hence the general solution is :
![y=y_c+y_p=e^(-2t)(c_1\cos 6t+c_2\sin 6t)-(25)/(148)(6\cos 6t-\sin 6t)](https://img.qammunity.org/2022/formulas/mathematics/college/3ed3uodebvtvigqmj2zruz4vo0ishj45ld.png)
Now we use given initial condition.
![y(t) &=e^(-2 t)\left(c_(1) \cos 6 t+c_(2) \sin 6 t\right)-(25)/(148)(6 \cos (6 t)-\sin (6 t)) \\\\\y(0) &=e^(-\alpha 0))\left(c_(1) \cos (0)+c_(2) \sin (0)\right)-(25)/(148)(6 \cos (0)-\sin (0)) \\\\0 &=\left(c_(1)\right)-(25)/(148)(6) \\\\c_(1) &=(75)/(74) \\\\y(t) &=e^(-2 t)\left(c_(1) \cos 6 t+c_(2) \sin 6 t\right)-(25)/(148)(6 \cos (6 t)-\sin (6 t)) \\\\](https://img.qammunity.org/2022/formulas/mathematics/college/bgm8y80wqav8fg95ls1zmjuznn0g7i2mrd.png)
![y^(\prime)(t)=-2 e^(-2 t)\left(c_(1) \cos 6 t+c_(2) \sin 6 t\right)+e^(-2 t)\left(-6 c_(1) \sin 6 t+6 c_(2) \cos 6 t\right)-(25)/(148)(-36 \sin (6 t)-6 \cos (6 t)) \\\\y^(\prime)(0)=-2 e^(0)\left(c_(1) \cos 0+c_(2) \sin 0\right)+e^(0)\left(-6 c_(1) \sin 0+6 c_(2) \cos 0\right)-(25)/(148)(-36 \sin 0-6 \cos 0) \\\\0=-2\left(c_(1)\right)+\left(6 c_(2)\right)-(25)/(148)(-6) \\\\0=-2 c_(1)+6 c_(2)+(75)/(74) \\\\0=-2\left((75)/(74)\right)+6 c_(2)+(75)/(74) \\\\](https://img.qammunity.org/2022/formulas/mathematics/college/ukccjxa2i6zpsujj0812dga3y8hvwtbx07.png)
![\begin{array}{l}0=-(150)/(74)+6 c_(2)+(75)/(74) \\\\(150)/(74)-(75)/(74)=6 c_(2)\end{array}](https://img.qammunity.org/2022/formulas/mathematics/college/2oos1m5ncsrk4036dqjycevy7y7jezo80n.png)
![\begin{array}{l}c_(2)=(25)/(148)\\\\\text { Substitute } c_(1) \text { and } c_(2) \text { in } y(t) \text { . Then }\\\\y(t)=e^(-2 t)\left((75)/(74) \cos 6 t+(75)/(148) \sin 6 t\right)-(25)/(148)(6 \cos (6 t)-\sin (6 t))\end{array}](https://img.qammunity.org/2022/formulas/mathematics/college/7sps27f8yma165dmj0ycu4fi8e7a5hk9gm.png)
(2)
![y(t)=e^(-2 t)\left((75)/(74) \cos 6 t+(75)/(148) \sin 6 t\right)-(25)/(148)(6 \cos (6 t)-\sin (6 t)) \\\\y(t)=\left((75)/(74) e^(-2 t) \cos 6 t+(75)/(148) e^(-2 t) \sin 6 t\right)-(25)/(148)(6 \cos (6 t)-\sin (6 t)) \\\\y(t)=(75)/(74)\left(e^(-2 t)-1\right) \cos 6 t+(25)/(148)\left(3 e^(-2 t)+1\right) \sin 6 t \\\\|y(t)| \leq (75)/(74) e^(-2 t)-1|\cos 6 t|+(25)/(148)\left|3 e^(-2 t)+1\right||\sin 6 t| \\\\](https://img.qammunity.org/2022/formulas/mathematics/college/do9g7jqbxna138ekjyf6gfovldqk52qhcq.png)
![|y(t)| \leq (75)/(74)\left|e^(-2 t)-1\right|+(25)/(148)\left|3 e^(-2 t)+1\right| \\\\\lim _(t \rightarrow \infty) y(t) \leq \lim _(t \rightarrow \infty)\left\(75)/(74)\left \\\\\lim _(t \rightarrow \infty) y(t)=\left\(75)/(74)\left \\](https://img.qammunity.org/2022/formulas/mathematics/college/bdkfqukxgh6n5kukuwgnqfbnrpk7629qi4.png)
![\lim _(t \rightarrow \infty) y(t)=\left\{(75)/(74)(-1)+(25)/(148)(1)\right\}=-(75)/(74)+(25)/(148)=-(-150+25)/(148)=-(125)/(148) \approx-0.844](https://img.qammunity.org/2022/formulas/mathematics/college/in1fjdqxrljcsvubn8vhvamv3erdurrx3z.png)